Adaptação transcultural e análise de propriedades de medida do Exercises Preference Questionnaire (STROKET)-BrasilL - Livia Cristina Guimaraes Caetano (2016)
The Exercises Preference Questionnaire (EPQstroke), specific for people with stroke, is designed to measure the personal factors that could influence the motivation and adherence to the practice of physical activities. It discriminates preferences, increases engagement and organizes programs related to the exercises for survivors stroke. The present study aimed at performing the translation and cross-culturaladaptation of the EPQ(stroke) to Brazilian Portuguese language and analyze its measurement properties. The original version was submitted to translation, synthesis, back-translation, expert committee review, and pre-testing process, according to recommended guidelines. The pre-final version was applied to 30 individuals with chronic stroke. Then, after the final version of the EPQ(stroke)-Brazil was created, its validity and reliability were tested. Test-retest reliability was verified using the Kappaindex and Intra-class Correlation Coeficcient (ICC) (n=50), and the internal consistency was assessed by Cronbach's alpha coefficient (n=101). Construct validity was assessed by the Confirmatory Factorial Analysis (n=101), content validity, by the content validity index (n=8), and, face validity, by the rate of agreement regarding the clarity of the wording, the ability to answer the questions, and the layout and style of the EPQ(stroke)-Brazil in two groups including individuals with stroke (n=81) and multidisciplinary health professionals (n=32). The pre-final version required review of the items 9, 29, and 30) and, after another pretest, itshowed to be appropriate. The Kappa indices ranged from 0,58 to 0,95; the ICC values ranged from 0,35 to 0,93, and the Cronbach's alpha coefficient was 0,82. The Confirmatory Factorial Analysis and the Content Validity Index confirmed the validity of the EPQ(stroke)-Brazil. The rate of agreement regarding clarity, the ability to answer questions, and the layout and style of the EPQ(stroke)-Brazil was greater than 80% forboth individuals with stroke and health professionals. Therefore, the EPQ(stroke)-Brazil showed to be a valid and reliable measure for the assessment of exercise preferences in individuals with chronic stroke, considering the personal factors described by the International Classification of Functioning, Disability and Health.